Role of magnesium in essential hypertension - Karim, M.d Fazlul; Singh, Harbindarjeet; Rahman, Abd Rashid Abd; Sirisinghe, R.G. (1999)
Beneficial role of magnasium supplementation in prevention of complications in coronary artery disease (Iseri,1984) in ischaemic heart disease (Altura,1988) and in the treatment of patients with AMI (Abraham,1990) has been well documented. One study showed that magnesium supplementation reduced arterial blood pressure in patients with hypertension (Dykner& Waster,1983).Renin profiling, nevertheless,has revealed higher,and lower magnesium levels in low renin and high renin hypertensives respectively (Resnick LM et a1 1983).The significance of this seems to be that the influence of magnesium intake on blood pressure may differ according to the underlying state of magnesium metabolism in hypertensive patients. These observations remain largely unconfirmed. Recently it has been reported that a disordered metabolism of magnesium and calcium ions is present in women with pregnancy induced hypertension (Singh, HJ 1993).So the objective of this study was to investigate the magnesium status in serum, erythrocyte and in urine of untreated hypertensive patients. Work was further extended to investigate the relationship between serum and urinary magnesium levels,plasma renin activity (PRA) and plasma renin concentration (PRC) in normotensive and age and sex-matched untreated hypertensives.